Boot camps: An alternative sanction for better or worse - Macdonald, Angela Dawn (2003)
In the past twenty years boot camps have been evaluated for effectiveness on reducing recidivism, crowding, and costs to the Departments of Corrections. Program and offender characteristics have been studied. This analysis intends to determine how well studied boot camps are, why there is so much disagreement in the findings, and what impact, if any, boot camp programming has had in corrections